Effect of pre-existing immobile dislocations on the evolution of geometrically necessary dislocations during fatigue. (23rd May 2017) - Irastorza-Landa, Ainara; Grilli, Nicolò; Van Swygenhoven, Helena
Abstract: The role of pre-existing mobile and immobile dislocation densities on the evolution of geometrical necessary dislocation densities (GNDs) during cyclic fatigue in shear is studied using a continuum dislocation-based model incorporated in a crystal plasticity finite element scheme. Clusters with different immobile dislocation densities are implemented in a homogeneous medium containing a certain mobile dislocation density. It is found that whether GND walls are formed around the initial immobile cluster (or not) strongly depends on the absolute values of initial mobile dislocation density and on the ratio between mobile and immobile densities. The results are discussed in terms of the apparent GND densities experimentally obtained using Laue micro-diffraction.